2011
DOI: 10.1007/s11262-010-0563-7
|View full text |Cite
|
Sign up to set email alerts
|

Unique evolution characteristics of the envelope protein of EIAVLN40, a virulent strain of equine infectious anemia virus

Abstract: The Chinese equine infectious anemia virus (EIAV) virulent strain EIAV(LN40) is derived from a naturally occurring virus by continuously passing in horses for 16 generations. Its genome sequence is 23% different from that of the American strains or the Japanese strains, and the variation of envelope gp90 surface unit (SU) is as high as 41%. In this study, evolutions of the EIAV(LN40) gp90 gene in four infected horses were analyzed. Results showed that new quasispecies arose in the early stage of infection in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…At the early phase of infection, we observed the appearance of clones containing S2 sequences clustered with the sequence of vaccine strains, which implies the selection of vaccine-like viral species in the quasispecies pool of EIAV, as well as the re-emergence of clones containing S2 sequences clustered with the sequence of EIAV LN40 strain at the late infection phase; this pattern of sequence clustering is correlated with typical EIA clinical symptoms. This tendency for in vivo evolution was observed in the S2 gene of all four horses examined in this study as well as in the previously examined gp90 gene [ 13 ]. This feature of EIAV in vivo evolution is consistent with the trophic change of HIV-1 in different infection phases and the re-boost of latent strains in clinically cured patients [ 18 ].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…At the early phase of infection, we observed the appearance of clones containing S2 sequences clustered with the sequence of vaccine strains, which implies the selection of vaccine-like viral species in the quasispecies pool of EIAV, as well as the re-emergence of clones containing S2 sequences clustered with the sequence of EIAV LN40 strain at the late infection phase; this pattern of sequence clustering is correlated with typical EIA clinical symptoms. This tendency for in vivo evolution was observed in the S2 gene of all four horses examined in this study as well as in the previously examined gp90 gene [ 13 ]. This feature of EIAV in vivo evolution is consistent with the trophic change of HIV-1 in different infection phases and the re-boost of latent strains in clinically cured patients [ 18 ].…”
Section: Discussionsupporting
confidence: 82%
“…Four horses were experimentally infected with a pathogenic EIAV strain, EIAV LN40 , in a previous study of the evolution of EIAV in vivo [ 13 ]. Two of these horses (#25 and #26) were inoculated with 1 × 10 6 TCID 50 EIAV LN40 and died of acute EIA at 28 and 30 days post infection (dpi), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrate that the primary source of dominant quasispecies in vaccines may not be clones arising from individual mutations but may instead be derived from an existing pool of quasispecies varieties. This hypothesis is supported by the phylogenetic analysis of all 596 unique LTR clones isolated in vitro and in vivo that is presented in this article, as well as by previous reports of in vivo evolution of the gp90 and S2 genes of LN40, which found that some viral clones isolated from certain phases of LN40-infected horses were identical or similar to the vaccine strains DLV121 and FDDV13 ( 30 , 31 ). These strains may account for a small proportion of the LN40 viral quasispecies and may be selected in response to changes in the intracellular environment.…”
Section: Discussionsupporting
confidence: 81%